Therapeutic Effect of Repetitive Transcranial Magnetic Stimulation Combined with Local Vibration Therapy on Children with Hemiplegic Cerebral Palsy - LI Mingdi; LIANG Guanjun; ZHANG Dali; ZHANG Hewei; WANG Wei; GU Qin (康复学报)
ObjectiveTo observe the effect of repetitive transcranial magnetic stimulation (rTMS) combined with local vibration (LVB) therapy on lower limb spasticity, balance function and gait function in children with hemiplegic cerebral palsy（HCP).MethodsA total of 66 children with HCP , who were treated in the Children's Hospital of Soochow University from January 2022 to December 2022 were randomly divided into control group, rTMS group and combined group, with 22 cases in each group. The control group received routine rehabilitation training (physical modality therapy, spasmodic muscle stretching training, postural transfer training, standing blance training and gait training, etc), 30 minutes a time, once a day, five days a week, lasting for twelve weeks. The rTMS group received low-frequency rTMS treatment additionally, with a frequency of five Hz and a stimulation intensity of 35% motor threshold (MT), the stimulation time of 10 s, and the interval of 20 s, 20 minutes a time, once a day, five days a week, lasting for 12 weeks. The combined group received LVB therapy in addition to the treatment of the rTMS group, and the vibration frequency was set to 15-20 Hz, within seven mm displacement, 10 minutes a time, once a day, five days a week, lasting for 12 weeks. Before and after treatment, the modified Ashworth scale (MAS) was used to evaluate the muscle tone; the balance subscale of Fugl-Meyer test (FM-B) was used to evaluate the balance function, and the Gait Watch three-dimensional gait analysis system was used to evaluate the three-dimensional gait parameters (stride speed, stride length, hip flexion, knee flexion and ankle flexion of the affected side).ResultsCompared with that before treatment, MAS scores of the rTMS group and the combined group after treatment decreased significantly, the FM-B scores and gait parameters (stride speed, stride length, hip flexion, knee flexion and ankle flexion of the affected side) increased significantly, and the differences were statistically significant (P<0.05). Compared with the control group, MAS scores of the rTMS group and the combined group after treatment decreased significantly, FM-B score, stride length and stride speed increased significantly (P<0.05); compared with the rTMS group, MAS score of the combined group after treatment decreased significantly, FM-B score and gait parameters (stride speed, stride length, hip flexion, knee flexion and ankle flexion of the affected side) increased significantly, and the differences were statistically significant (P<0.05).ConclusionThe rTMS combined with LVB therapy can effectively improve the lower limb spasticity, balance function and gait function of children with HCP, which is recommended for clinical application.